2002
DOI: 10.1046/j.1365-2044.2002.2366_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐controlled epidural fentanyl following spinal fentanyl at Caesarean section

Abstract: SummarySpinal fentanyl can improve analgesia during Caesarean section. However, there is evidence that, following its relatively short-lived analgesic effect, there is a more prolonged spinal opioid tolerance effect. The effectiveness of postoperative epidural fentanyl analgesia may therefore be reduced following the use of spinal fentanyl at operation. This randomised, double-blind study was designed to assess whether patient-controlled epidural fentanyl could produce effective analgesia following 25 lg of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The latter in particular was an important finding because as far as we know this is the first human study showing the concurrent administration of fentanyl by both spinal and systemic routes. Cooper et al (6) showed that epidural fentanyl produced more effective analgesia after the use of spinal fentanyl during Caesarean section. A number of animal studies have reported that the combined administration of spinal and systemic µ‐opioid agonists can produce a synergistic antinociceptive effect (5, 7, 8).…”
Section: Discussionmentioning
confidence: 99%
“…The latter in particular was an important finding because as far as we know this is the first human study showing the concurrent administration of fentanyl by both spinal and systemic routes. Cooper et al (6) showed that epidural fentanyl produced more effective analgesia after the use of spinal fentanyl during Caesarean section. A number of animal studies have reported that the combined administration of spinal and systemic µ‐opioid agonists can produce a synergistic antinociceptive effect (5, 7, 8).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19]21,22,24 Differences in the cumulative intraoperative opioid dose could at least partially explain the divergent findings. Focusing on studies administering remifentanil indicates that aggravated postoperative pain and/or increased opioid consumption was consistently reported if patients received a cumulative dose greater than 50 µg/kg but could not reliably be detected if patients received a smaller cumulative dose (Fig 2).…”
Section: Increased Postoperative Pain And/or Opioid Consumptionmentioning
confidence: 99%
“…125 Intravenous PCA was used for the comparison of locoregional and spinal techniques, for example, epidural analgesia with morphine or bupivacaine, each in combination with clonidine, 126 spinal anesthesia with bupivacaine and intrathecal or oral clonidine, 127 intrathecal morphine and sufentanil, 128 intrathecal morphine and bupivacaine, 129 or spinal anesthesia versus iliohypogastric-ilioinguinal peripheral nerve block. 130 Drug interactions during PCEA were studied for spinal bupivacaine and fentanyl, 131 epidural bupivacaine or ropivacaine alone 132 or in combination with morphine, 133 epidural bupivacaine or ropivacaine with sufentanil, [134][135][136][137] or for sufentanil dose finding for ropivacaine supplementation. 138 To investigate effective methods for reducing postoperative nausea and vomiting during opioid PCA, cyclizine, 139 dexamethasone, 140 or ondansetron 125,139,141 were tried with varying success rates.…”
Section: Patient-controlled Analgesia For Clinical Researchmentioning
confidence: 99%